Radiation Monitoring of an Isolation Room for 131I Therapy After the Patients Were Released. Issue 4 (October 2019) - Karo, Choeung; Ideguchi, Reiko; Nishi, Kodai; Fukuda, Naoko; Miura, Miwa; Matuda, Naoki; Kudo, Takashi
Abstract : Abstract: Purpose: This study was performed to obtain a better understanding of the radiation environment in an 131 I isolation room after the release of patients with metastasis from thyroid cancer that were treated with 131 I doses ranging from 3.7 GBq (100 mCi) to 5.5 GBq (150 mCi) because there have not been any previous studies regarding the ambient radiation levels encountered in 131 I isolation rooms after patients are released. Methods: Ambient radiation levels and total and removable surface contamination levels were monitored for 3 weeks after each patient's release (and before the entry of the next patient). An area located 0.75 m along the corridor outside the room, the door, window, bedside, and the wall of the shower room were monitored with a Nal scintillation survey meter, which was used to obtain readings of the ambient radiation level in six directions, and the mean value for each area was recorded. In addition, areas that were suspected to be highly contaminated, including the toilet bowl, toilet sink, bed head, back of the bed, sink, trash box, and the patient's pillow, were monitored for total surface contamination with a GM survey meter. Furthermore, the toilet's U-bend, toilet sink, bed guard, table, shielding, sink plug, and door knob were swabbed for monitoring removable surface contamination, which was measured using a well counter. Conclusion: Ambient radiation monitoring in an 131 I isolation room showed that there was negligible risk of harm in terms of the occupational radiation dose level after patients were released. The ambient radiation dose rate was higher near the door because the sink and trash box were located nearby. The toilet bowl, the toilet's U-bend, and the area around the sink exhibited heavy surface contamination, so these areas require cautious hygiene management.